2020
DOI: 10.1155/2020/2098315
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriospermia and Sperm Quality of Cryopreserved Bull Semen Used in Artificial Insemination of Cows in South Wollo Zone, Ethiopia

Abstract: The objectives of this trial were to estimate prevalence of bacteriospermia, to determine the bacterial load, and to isolate the types of bacteria as well as to assess the association between bacterial load and sperm quality traits in cryopreserved bull semen in field conditions in the South Wollo Zone. A total of 309 cryopreserved straws of semen from the Holstein Friesian (HF)-cross bull (n = 180 straws) and pure Jersey bull (n = 129 straws) were investigated. Bacteriological assessments of the presence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…The relatively high load in our field ejaculates may explain why our semen samples showed lower seminal parameters than in other studies [9][10][11][12][13]. CFU correlates negatively with sperm motility, viability, and morphology [60]. Similarly, we observed a negative timedependent correlation between CFU and viability.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The relatively high load in our field ejaculates may explain why our semen samples showed lower seminal parameters than in other studies [9][10][11][12][13]. CFU correlates negatively with sperm motility, viability, and morphology [60]. Similarly, we observed a negative timedependent correlation between CFU and viability.…”
Section: Discussionsupporting
confidence: 51%
“…Semen collected at Semen Stations inevitably contains ambient microorganisms, up to 2.36 × 104 ± 1943 CFU/mL in fresh semen [57] and 1.00 × 10 ± 90 CFU/mL in frozen semen after thawing [58]. Other authors found 103-106 CFU/mL in five bulls analysed after collection at an insemination centre [59] and 50.38 ± 16.29 CFU/mL in thawed cryopreserved bull semen collected under field conditions [60]. A recent study [61] isolated 135 microorganisms from 25 genera from 174 frozen-thawed semen collected from artificial vaginas and analysed at different periods of the conservation process.…”
Section: Discussionmentioning
confidence: 99%
“…Production and dissemination of microbe‐free quality semen are the major objectives of semen collection centres throughout the world, and the success of artificial insemination (AI) depends on the quality semen production and logistics (Reda et al., 2020). It is also envisaged that bacterial load in semen is considered as one of the major concerns, which affects the semen quality, and further fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased sperm concentration (Bezold et al., 2007), loss of motility (Moretti et al., 2014), sperm morphological alterations (Diemer et al., 2000), sperm viability (Domes et al., 2012) and impairment of acrosome reaction are the most frequent alterations seen in spermatozoa attributable to bacteria in both in vivo and in vitro conditions. Other mechanisms by which bacterial contamination in semen affects fertility is the altered mitochondrial function, which leads to formation of reactive oxygen species hereby provoking DNA damage (Reda et al., 2020). On the other hand, the resultant infiltration of leucocytes into the site of infection may be associated with the additional risk factor and is also responsible for alteration of sperm fertilising capability, due to oxidative, apoptotic and immune processes (Moretti et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation